EVALUASI DAYA DUKUNG EKONOMI BUDIDAYA KERAPU (FAMILI SERRANIDAE) DI PERAIRAN PULAU PONGOK KABUPATEN BANGKA SELATAN - SUDIRMAN ADIBRATA (Akuatik: Jurnal Sumberdaya Perairan, 2013)
Floating Net Cage (FNC) system were applied to mariculture of groupers (Family Serranidae) in marine waters of Pongok Island, Regency of South Bangka. The economic carrying capacity of the system have been evaluated based on R/C, NPV, PP, and IRR analysis. The result revealed that FNC system still gives a big opportunity as an alternative income for the local residents since it provides a multiplier effect to 127 households in the basic of symbiotic mutualism. Area suitability for grouper mariculture in Regency of South Bangka estimated only used about 0,5% of waters which provides the economic advantage for 127 households, or about 4,3% of 2.959 fishermen in the District of Lepar Pongok. Economic carrying capacity proved to be positively correlated with social carrying capacity to move the economy in the small island with reef fishery resources like Pongok Island. The government policies needed in order to support the FNC system as an economic prime mover in the coastal area or small island with potential reef fishery like in Pongok Island